STRATEGI PENJUALAN DI MARKETPLACE SHOPEE UNTUK MENINGKATKAN PENJUALAN SEPATU KULIT PADA 10 UMKM DI CIBADUYUT BANDUNG - Ely Suhayati; Nizar Nugraha Supriatna (Universitas Trisakti, 2022)
The existence of PPKM due to Covid-19 has made MSMEs the most affected due to losing purchasing power, because people are afraid of contracting the virus so they cannot shop directly to the store, in order to survive, MSMEs must be able to use technology to increase sales through the marketplace so that people can shop online. MSME who utilizes technology in their business, prove to be stronger in facing of the external shocks. The purpose of this community service is how MSMEs can apply how to design, upload, and create promos in the shopee marketplace as a product sales strategy. The method used qualitatively using interviews and observation techniques with the delivery of material using the zoom meeting application. The result of community service is training on how to design advertisements, then uploading them and making promos virtually in addition to using the Zoom Meeting application, also providing Video Files in the form of E-Course Marketplace Shopee, as well as providing consultation via Whatsapp without a time limit if there are difficulties when implementing it for 10 MSMEs Shoes in Cibaduyut. Conclusion 10 Leather Shoes’s MSMEs in Cibaduyut after training in virtual application using the zoom meetings were able to design a shop in the marketplace shopee and upload the photos of their product and make promos to attract more buyers to introduce Local Brand means that 10 MSMEs Shoes Cibaduyut able to apply to advertise in shopee for sell more products so as to increase sales, through selling strategies in the marketplace.